PERAN TEKNOLOGI & WEB DALAM AKUNTANSI - Totok Dewayanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
Technological developments changed methods for carrying out tasks within the scope of accounting activities and transactions related to accounting was started to being carried out through electronic media. Growth and development growing rapidly in information technologies day by day have brought digital revolution in economic, social and cultural fields.This era is information era and when we acknowledge that accounting is an information system, the way and processes of transacting businesses of enterprises have changed with usage of information technologies in enterprises and this influenced accounting closely. Necessity of keeping up with changing conditions of accounting led educators and practitioners to new pursuits.Enabling inclusion of information era and technologic factors in education by benefiting from digital resources as well as theoretical information in accounting education provided in universities and generating an interactive environment to keep student wakeful and preferring educational model in which information technologies are used is necessary. In order to achieve that, students should be provided to take target-driven accounting courses and an educational order should be generated in which students can evaluate and interpret information beyond recording and make difference through information and communication technologies.One of digital applications produced on this issue is E-accounting. E-accounting is perception of enabling management of all activities more efficiently, affordably, flexibly than before through facilities of internet. All parties of the activity (employee-manager-customer-public body-business partner-supplier) are real-time users of the system and those sharing up-to-date information instantly.Accounting staffs that can apply this structure in enterprises through accounting education and establish this system in enterprises are needed. Therefore, quality of accounting education is a factor influencing success of employees of enterprises and hence enterprises directly. Re-structuring of accounting education and developing contents by considering present conditions are necessary with respect to train graduates having sufficient quality to respond needs of this era.